EFEKTIVITAS BERBAGAI WAKTU INJEKSI PGF2α SEBELUM PENAMPUNGAN SPERMA DOMBA LOKAL TERHADAP KUALITAS SPERMA DALAM PENGENCER TRIS YANG DISIMPAN PADA SUHU 5°C: EFFECTIVITY OF VARIOUS TIME INJECTION OF PGF2α BEFORE COLLECTED SPERM OF LOCAL SHEEPS ON SPERM QUALITY USING TRIS DILUTION SAVED IN TEMPERATURE OF 5°C - . Purwaningsih; . Sunardi (Fakultas Peternakan Universitas Papua, 2010)
This experiment aimed to evaluate the effect of PGF2α and time of injection on the quality and viability of Local ram sperm in Tris dilution at 50C storage temperature. The sperm was collected from four Local rams with artificial vagina, once a week for one month. At the first week, sperm were collected without PGF2α injection; 10 minute after PGF2α injection in second week; 20 minute after PGF2α injection in third week; and 30 minute after PGF2α injection in fourth week. PGF2α with dose of 1,0 ml/head (7,5 mg Luprostiol/ml) were given by intramuscular injection in thigh area. The data were analyzed by Completed Randomized Design. When there were significant differences continued with Duncan’s New Multiple Range Test. The result showed that PGF2α injection significantly (p<0.05) increased the motility sperm and life sperm percentage especially on collected sperm 10 minute after PGF2α injection. Ejaculate volume, pH, sperm concentration, abnormal sperm percentation and sperm viability, showed no significant difference (p>0.05). Based on the result of this study, it was concluded that PGF2α injection 10 minute before sperm collection could improve sperm quantity and quality specifically sperm motility and sperm life percentation.